Fixed point theorems of nonlinear contractions on p-quasi-cone metric space - Sila, Eriola Belul (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we have proved some results of fixed point on p-quasi cone metric spaces. The p-quasi cone metric space is a generalization cone metric space. Kiany and Amini-Harandi[1] have given a generalization of Ciric contraction[2]. In this paper we give a generalization of result [2] for p-quasi-cone metric space.